2016
DOI: 10.1186/s12883-016-0667-3
|View full text |Cite
|
Sign up to set email alerts
|

Small (autonomic) and large fiber neuropathy in Parkinson disease and parkinsonism

Abstract: BackgroundRecent studies have reported that peripheral neuropathy (PN) is common in patients with Parkinson’s disease (PD) and raised the possibility that levodopa neurotoxicity is the main culprit.MethodsWe evaluated the presence of large & small (autonomic) fiber PN in 54 consecutive patients with PD or parkinsonism in a tertiary outpatient clinic from Brazil. Initial PN screening consisted of history/neurological exam and skin wrinkling test (SWT). In addition, we also performed Nerve conduction studies/Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…Age and PD duration contribute indirectly to the severity of PNP in PD. Nonetheless, a clear link between PD duration, age, and PNP in PD, relations that were albeit revealed in other published studies [6,7,8,9,15,52], could not be established in the present work. On the other hand, the risk for PNP was not stratified, in contrast to the study of Ceravolo et al [15].…”
Section: Discussioncontrasting
confidence: 82%
“…Age and PD duration contribute indirectly to the severity of PNP in PD. Nonetheless, a clear link between PD duration, age, and PNP in PD, relations that were albeit revealed in other published studies [6,7,8,9,15,52], could not be established in the present work. On the other hand, the risk for PNP was not stratified, in contrast to the study of Ceravolo et al [15].…”
Section: Discussioncontrasting
confidence: 82%
“…SFN has been reported in patients with Gaucher disease as possible explanation for neuropathic origin of chronic pain [65]. Finally, SFN has been also described in association with disorders characterized by widespread pain such as fibromyalgia [5] and Ehlers-Danlos syndrome [66], and in neurodegenerative diseases like Parkinson's disease [14][15][16][17][18][19][20][21] and ALS [10][11][12][13].…”
Section: Causes Of Sfnmentioning
confidence: 99%
“…The introduction of skin biopsy, which allows a reliable quantification of intraepidermal nerve fiber density (IENFD), has been a milestone for the diagnosis of SFN [8,9]. In the following decades, a flourishing of studies widened the spectrum of diseases associated with small nerve fiber degeneration, from painless amyotrophic lateral sclerosis [10][11][12][13] and Parkinson's disease [14][15][16][17][18][19][20][21] to painful erythromelalgia [22]. These findings further emphasized that the diagnosis of SFN cannot disregard the clinical context and the accurate characterization of patients' phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is easy to use and inexpensive. However in this study, it remained unclear to what degree observed differences in wrinkling of the skin did reflect postganglionic small nerve fiber function rather than large fiber integrity limiting interpretability of the results ( 22 ).…”
Section: Introductionmentioning
confidence: 89%